Oxidative enzyme-based optical biosensors for detection of substituted phenols in environmental samples - Espiña, Marietta L.
Tyrosinase-based fiber optic biosensor and bilirubin oxidase-based flow injection biosensors were developed for quantification of phenols and pentachlorophenol, respectively. The application of these biosensor systems in environmental monitoring was also studied. Tyrosinase was immobilized in a polythersulfone membrane mounted in a reaction cell couples with fiber optics connected to a miniaturized spectrophotometer. The miniaturized spectrophotometer operates in visible range using diode optimized at 565 nm, with the enhancement of absorbance of the chromophoric product by barbituric acid. Under optimum conditions, this biosensor system gave linear responses to phenol, catechol and p-cresol up to 0.3 mM (phenol and catechol) and 0.2 mM (p-cresol). The detection limit (S/N = 3) was determined to be 0.01 mM for catechol and phenol, and 0.1 mM for p-cresol. Bilirubin oxidase (BOX) was immobilized in aminopropyl glass beads and the flow injection (FI) biosensor system for pentacholorophenol (PCP) was designed using a substrate recycling scheme. PCP was efficiently converted to 1,4-tetracholoro-p-benzoquinone (1,4-TCBQ) and then to 1,4-tetrachloro-p-hydroquinone (1,4-TCHQ) by bis(trifluoroacetoxy)iodobenzene (BTFAIB) and zinc powder, respectively. BOX rapidly oxidized 1,4-TCHQ to 1,4-TCBQ, which in turn was readily reduced back to 1,4-TCHQ in the presence of excess β-Nicotinamide Adenine Dinucleotide (NADH). Under optimized conditions the rate of NADH consumption, measured as the absorbance decrease at 340 nm, yielded a 1,4-TCHQ detection limit of 250 nM. The detection limit was improved to 25 nM by using a fluorescence detector with excitation and emission wavelengths of 345 and 450 nm, respectively. Water samples spiked with phenol were analyzed using the tyrosinase-based fiber optic biosensor while PCP contaminated soil samples were analyzed using the bilirubin oxidase-based flow injection biosensor. The results comapred well with the reference methods. The tyrosinase-based biosensor system is nonspecific to phenol; but it can be useful for fast contaminant monitoring and screening. The bilirubin oxidase-based biosensor system is substrate specific to 1,4-TCHQ and, or 1,4-TCBQ
Research project funded by the University through the Office of the Vice-Chancellor for Research and Development (OVCRD)
"October 2006."
Thesis (Ph.D. Environmental Science)--University of the Philippines Diliman
Keywords: Phenols -- Environmental aspects; Biosensors; Environmental monitoring